Perilaku Digiseksual dalam Al-Qur’an - asih, wiji nur (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Institut Agama Islam Negeri (IAIN) Purwokerto, 2020)
In this most recent era, sexuality has found a new form that is inseparable from the sophistication of technology that shapes the face of sexual digitalization / digisexuality. This research seeks to describe Al-Qur'an's view of digital behavior from the perspective of Maqashid Syari'ah Al-Ghazali. This research was conducted using qualitative methods and taking data from various literature (library research). In this study, the writer used the theory of maqÄá¹£Ä«d al-syarÄ«'ah which was initiated by Al-Ghazali to analyze the verses about sexuality to obtain Al-Qur'an's view on digisexuality. The results of this study indicate that digital behavior when viewed from the aspects of Maqashid Al-Syar'ah, including protection of the soul, mind, religion, descent, and property has many shortcomings and does not achieve the purpose of sexuality by the guidance of the Al-Qur'an.